Fusarium species and assessments of mycotoxin (deoxynivalenol), in wheat seeds from different regions of Türkiye - Kubra SARACOGLU; Greice Amaral CARNEIRO; Eleonora CAPPELLETTI; Fatma Sara DOLAR; Antonio PRODI (Phytopathologia Mediterranea)
Wheat cultivation is important in Turkish agriculture, which ranks 10th among international wheat producers, and is an important wheat exporter, particularly to Europe. Fusarium-related threats, such as Fusarium Head Blight (FHB) and Fusarium Crown and Root Rots (FCR, FRR), and related mycotoxin seed contamination, jeopardize product quality. This study analysed 65 wheat seed samples for presence of Fusarium species, from cultivars of Triticum aestivum (bread wheat) and T. durum (durum wheat) collected from seven regions of Türkiye. PCR with specific primers, and phylogenetic analyses of TEF1-α segments, discriminated Fusarium species. Levels of the mycotoxin deoxynivalenol (DON) in flour samples were also evaluated. Out of 195 Fusarium isolates, the prominent species included F. graminearum (32% of isolates), F. proliferatum (16%), F. avenaceum (11%), F. clavum (11%), and F. verticillioides (7%). Less frequently isolated species were F. oxysporum (6%), F. acuminatum (3%), F. ramigenum (3%), F. culmorum (3%), F. poae (2%), F. sambucinum (2%), F. tricinctum (2%), Fusarium sp. FTSC12 (2%), F. andiyazi (1%), and F. equiseti, F. incarnatum, and F. fasciculatum (each 0.5%). Five of the 65 samples tested positive for DON, with two exceeding the European Commission threshold for mycotoxin contamination; one bread wheat from the Black Sea region, known for its annual rainfall, and a durum wheat sample from southeastern Anatolia, which had the highest detected DON level of 1730 μg kg-1. Among these samples F. graminearum was the predominant species. As F. andiyazi and F. ramigenum are not normally associated with wheat plants, a pathogenicity test was conducted with two isolates of each of these species, revealing no pathogenicity on the durum wheat cultivar ‘San Carlo’. These results provide a basis for managing fungal threats and mycotoxin contamination, safeguarding the quality of wheat grain as an essential agricultural product.